2019
DOI: 10.3390/jcm8040508
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Transcranial Magnetic Stimulation Therapy (rTMS) for Endometriosis Patients with Refractory Pelvic Chronic Pain: A Pilot Study

Abstract: Endometriosis concerns more than 10% of women of reproductive age, frequently leading to chronic pelvic pain. Repetitive transcranial magnetic stimulation (rTMS) over the primary motor cortex (M1) induces an analgesic effect. This effect on chronic pelvic pain is yet to be evaluated. The objective of this study was to assess the feasibility and effect of rTMS to reduce pain and improve quality of life (QoL) in patients with chronic pelvic pain due to endometriosis. This pilot, open-labelled prospective trial e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…Before the first session of iTBS, the individual resting motor threshold (RMT) was examined for each subject following the procedure as follows: first, the motor evoked potential (MEP) was measured from the hemiplegia abductor pollicis brevis muscle with surface electrodes (patients with unmeasured MEP on the hemiplegic side are measured with the contralateral side) [ 38 ], and then, the “hotspot” was determined using single-pulse TMS over the primary motor area (M1) where the largest MEP was evoked; then, the single-pulse TMS was given at the “hotspot” from low intensity, and with a stepwise increasing intensity until the amplitudes of 5 out of 10 trials exceeding 50 mV; this intensity was defined as the individual RMT. The hotspot location was marked on a positioning cap for each participant, which the participant wore while receiving iTBS over the M1 area [ 31 , 39 ]. After determining the RMT and stimulation point for each subject, the first session of left M1 iTBS was performed with the following parameters: intensity of 80% RMT, three pulses at 50 Hz in each burst at 5 Hz, and 2 s stimulation with 8 s interval; a total of 800 pulses were delivered for one session.…”
Section: Methodsmentioning
confidence: 99%
“…Before the first session of iTBS, the individual resting motor threshold (RMT) was examined for each subject following the procedure as follows: first, the motor evoked potential (MEP) was measured from the hemiplegia abductor pollicis brevis muscle with surface electrodes (patients with unmeasured MEP on the hemiplegic side are measured with the contralateral side) [ 38 ], and then, the “hotspot” was determined using single-pulse TMS over the primary motor area (M1) where the largest MEP was evoked; then, the single-pulse TMS was given at the “hotspot” from low intensity, and with a stepwise increasing intensity until the amplitudes of 5 out of 10 trials exceeding 50 mV; this intensity was defined as the individual RMT. The hotspot location was marked on a positioning cap for each participant, which the participant wore while receiving iTBS over the M1 area [ 31 , 39 ]. After determining the RMT and stimulation point for each subject, the first session of left M1 iTBS was performed with the following parameters: intensity of 80% RMT, three pulses at 50 Hz in each burst at 5 Hz, and 2 s stimulation with 8 s interval; a total of 800 pulses were delivered for one session.…”
Section: Methodsmentioning
confidence: 99%
“…Our search identified one RCT (100), one prospective observational study (102), and one case report (101) that investigated the efficacy of rTMS for treating pelvic pain. In a crossover RCT conducted by Cervigni et al (100), 13 patients were randomized into two groups.…”
Section: Pelvic Painmentioning
confidence: 99%
“…In the same year, Nizard et al (101) reported successful application of 1-Hz rTMS delivered on the DLPFC region of both hemispheres in one patient, which resulted in complete resolution of suprapubic pain and a dramatic decrease in micturition frequency. Most recently, in 2019, Pinot-Monange et al (102) prospectively enrolled 12 patients with refractory CPP caused by endometriosis. After five 10-Hz rTMS sessions targeting the left M1 over the hand representation, nine patients reported pain improvements as measured by the VAS score, and these improvements lasted up to 28 days.…”
Section: Pelvic Painmentioning
confidence: 99%
“…Our findings are in line with 2 recent studies of rTMS on female patients. Pinot-Monange et al [22] studied the effect of rTMS on chronic pelvic pain due to endometriosis and showed a maximum of a 1-point decrease in visual analogue scale (VAS) scores at 28 days of follow-up. In a study by Cervigni et al [13], rTMS significantly decreased VAS scores in patients with BPS/IC, while sham treatment showed no significant effect on any parameters.…”
Section: Injmentioning
confidence: 99%